Secondary ion emission from ethanol microdroplets induced by fast heavy ions. (November 2015) - Majima, T; Kitajima, K; Nishio, T; Tsuchida, H; Itoh, A
Abstract: We have developed a new experimental setup that allowed us to study collision interactions between fast ions and liquid microdroplets under a high vacuum condition. Microdroplets of ethanol are irradiated with 1.0-MeV H + and 2.0-MeV C 2+ ions. The size distribution of the droplets is evaluated from energy-loss measurements of projectile ions penetrating through the microdroplets. We obtain time-of-flight mass spectra of secondary ions from ethanol droplets. It is demonstrated that coincidence measurements with secondary electrons can distinguish specific ions produced in collisions with the droplets. Production mechanisms of H3 O +, C4 H9 O +, (C2 H5 )2 OH + in the liquid ethanol are discussed.